Utilización de antimicrobianos en pacientes hospitalizados en el servicio de pediatría del hospital Regional Docente de Trujillo en el período de enero – marzo del 2006 - Burgos Villuaneva, Wilder Alex (2006)
Objective: To evaluate the characteristics of use of antimicrobial (ATM) in the service of hospitalization of Pediatry of the Hospital Regional Docente de Trujillo. Material and Methods: A descriptive, cross-sectional, prospective study was made that included to the patients hospitalized during the months of January March of the 2006. This service counts on a total of 36 beds. I consider myself to all the patients hospitalized in this period. The evaluation of the quality of the prescription was made by a physician pediatrist; in addition it was used bibliographical sources. Results: 136 patients and their respective clinical histories included themselves. The prevalence of the prescription of antimicrobial (PPA) was 72.79 %. The average of prescription of antimicrobial by hospitalized patient was 1,46. The profile of ATM consumption demonstrates a monthly increase in the use, with a coefficient of correlation a 0,96 and approximated coefficient of regression of 3,40 DDD/100 bed-day. In relation to the indications for the administration of the medicine, these were made correctly as far as the used dose (87.59%), interval of use (97.24 %) and via of administration (100.00 %). A prescribed 92% of the antimicrobial ones belong to the Petitionary National Essential Medicines (PNEM). Conclusions: The PPA and average of ATM by patient are within the ranks reported in other studies; the ATM consumption demonstrates a monthly increase in its use; most of used ATM it belongs to the PNME, on the other hand the use of ATM according to criteria of established use is inside acceptable values